An evaluation of the RecycleNSave initiative in Singapore - Ho, Xin Rui (Nanyang Technological University, 2023)
In an attempt to raise recycling rates in Singapore, the RecycleNSave initiative was launched in 2019 to collect recyclable plastic bottles and aluminium cans using automated Reverse Vending Machines (RVM) that reward participants for their efforts in recycling. Despite four years having passed since the initiative began and the recent announcement of the upcoming Beverage Container Refund Scheme which has similar objectives, there is a lack of literature examining the effectiveness of this ongoing initiative. This study hence evaluates the effectiveness of RecycleNSave in encouraging recycling behaviours, particularly amongst youths. Using the Theory of Planned Behaviour, analysis of results collected from interviews and a survey found that the initiative was not effective, owing to a lack of change in attitudes and perceived behavioural control over recycling. This paper also identifies flaws in the design and implementation of RecycleNSave, and proposes recommendations to improve its effectiveness through increasing publicity efforts, change in reward options, lowering of redemption criteria, change in location of RVMs and introducing data-based scheduled checks on RVMs.